Refractory epilepsy in preschool children with tuberous sclerosis complex: Early surgical treatment and outcome. (August 2018) - Fohlen, Martine; Taussig, Delphine; Ferrand-Sorbets, Sarah; Chipaux, Mathilde; Dorison, Nathalie; Delalande, Olivier; Dorfmüller, Georg
Highlights: Early surgery is highly effective in preschool children with TSC and drug resistant epilepsy. Earlier surgery, possibly during the first 2 years of life, has the greatest benefit. Successful surgery contributes to impressive cognitive improvement and might prevent ASD. Abstract: Purpose: Epilepsy surgery has been shown to be effective in treating focal epilepsy related to tuberous sclerosis complex (TSC). We analyzed the advantage of early surgical management in terms of seizure frequency and development. Method: We retrospectively studied the 15 patients younger than 6 years who underwent resective surgery between 2006 and 2016. Fourteen of them had invasive monitoring while the 15th was operated on under corticography. Results: Epilepsy began before 5 months of age in all patients. Overall 13 patients (86%) had a dramatic improvement of epilepsy after surgery (Engel 1 and 2) including 9 patients (60%) seizure free (Engel 1 A). In the group of 9 patients younger than 20 months at the time of surgery who presented with catastrophic epilepsies, 77% are Engel 1 A and the other 23% Engel 2. In this subpopulation, no one developed autism and four (44%) regained normal development. Conclusions: In early onset epilepsies associated with TSC, surgical treatment is highly effective, in particular when performed early. Invasive monitoring contributes to the successful outcome. Those data have to be confirmed by multicentric studies including quantitative analyses of the recordings.